Economics of innovation: competition, clubs and the environment - Walter, Jason (Kansas State University, 2015)
Innovation is development of new ideas that leads to better solutions to current problems. From an economic standpoint, innovation is the engine of economic growth. The appearance of innovation is not uniform in the market, and neither are its affects. The development of new products and technology is significant in any industry. As a result, understanding the path of progress within an industry is necessary to maximize the benefit from innovation. The focus of this research is to further understand the relationship between producers, consumers, and the environment, in the context of innovation. Three scenarios are evaluated. First, innovation evaluated in the context technology intensive industries with product differentiation. Using an optimal control approach with product differentiation and firm outlook we examine conditions that maximize social welfare. When firm(s) have the same discount rate regardless of market structure, a monopoly will develop more innovative products. However, it is shown that competition may increase innovation if firms alter their outlook in a duopoly market structure. Next, influence of consumers on producer adoption of clean technology is evaluated. A spatial model is developed to analyze welfare implications of environmental policies in a competitive market with production and consumption heterogeneity. Consumers with heterogeneous preferences choose between non-green and certified green products, while firms with heterogeneous production costs decide whether to engage in green production. In order for green products to be recognized by consumers, firms must join a green club. The number of green firms, environmental standard, and overall welfare under the market solution are all found to be socially sub-optimal. Finally, producer innovation in markets characterized by public policy due to emission concerns is evaluated. Using a dynamic approach, we derive a firm’s optimal R&D investment strategy to develop clean technology. Explicitly allowing for the cumulative nature of R&D shows that emissions per unit of output are lowest when the firms cooperate in R&D, and show that a profit-maximizing merged entity will never choose the most efficient investment strategy in clean technology, which has implications for emission tax policy and environmental innovation to improve overall welfare.
Keywords: Eco-certification; Clubs; Innovation; Dynamic R&D; Environmental regulation; Product appeal; Economics (0501); Economic Theory (0511); Environmental economics (0438)